Função Quadrática: um estudo didático de uma abordagem computacional - Maia, Diana (2007)
This research aims to supplement the studies that have already been conducted in regard to teaching quadratic functions as well as the utilization of software that support this teaching. It also aims to consider graphs of quadratic functions by making use of the global interpretation of the properties of images, as well as by adding a playful dynamic to initiate students into the notion of interval and function domain. The study has its theorectical roots based on the principles of Didactic Engineering and Raymond Duval´s Theory of Semiotic Representation Registers and Guy Brousseau s Theory of Didactical Situations. The didactic studies presents some brief analyses of some primary and middle school level didactic books and builds upon Benedetti s research (2003) about the utilization of graph software as well as Duval s research (1998) about the articulation problems between the graphical and algebraic registers. The computer-based tool used for the application of this study was Winplot. The study was carried out with private school students undergoing the 8th grade in the City of São Bernardo do Campo in the state of São Paulo. Data from four pairs that took part in seven research sessions were reviewed. Results reveal that an improvement was obtained and better retention was measured amongst students in regards of the square function concept, which was achieved by the articulation between visual variables and meaningful symbolic units